An Investigation of Biology Lab at Secondary Level in District Mardan - Inam Hussain,; Dr. Hafiz Muhammad Irshadullah,; Dr. Saqib Shahzad, (Dialogue Social Science Review (DSSR), 2025)
An Investigation of biology lab at secondary level in district Mardan was a new study. In this study the following research objectives and research questions were used: (1) To investigate basic facilities related to biology lab at secondary level in district Mardan; & (2) To inquire about biology lab equipment at secondary level in District Mardan. while (1) What are the basic facilities related to biology lab at secondary level in district Mardan? & (2) What is the biology lab equipment at secondary level in district Mardan? This study is very significant for the science students at secondary level in Khyber Pakhtunkhwa. All the Public Sector Science Secondary School in District Mardan was the population. A sample of (51) government School teachers in district Mardan was selected randomly. In which the following respondents were included. Closed-ended questionnaire was used. The experts verified the tool. Instrument reliability was determined to be 0.80. This study was delimited to all the public sector science secondary teachers in District Mardan. It was concluded that biology labs have enough space, light, proper hygiene, experimental tables, whiteboards, safety kits, microscopes, beakers, test tubes, funnels, magnifiers, and balances. It was recommended that biology laboratories be upgraded according to the teachers & students’ needs on a regular basis. Furthermore, Teachers & students may be properly trained to use laboratory items.